Passive Rom Therapy to Improve Muscle Strength in Post-Op Upper/Lower Extremity Patients: a Case Study - Musa Bangkit Alfaruq; Arina Maliya (International Journal of Health and Medicine, 2024)
Fractures are emergency conditions that must be treated quickly and accurately and in accordance with fracture management procedures. In general, clients with fractures must undergo surgery which in addition to causing pain also affects activity. After surgery, rehabilitation is needed to prevent contractures. Nursing care for patients with upper/lower extremity fractures must be prioritized and focused on providing comfort, preventing complications, and achieving optimal rehabilitation in rehabilitation. Patients are taught mobilization or movement exercises, namely Passive Range of Motion (ROM). Purpose: To determine the Effectiveness of Passive ROM Exercise in Postoperative Patients with Upper/Lower Extremity Fractures on Length of Stay at Sukoharjo Regional General Hospital. Design: This researcher studied the type of experimental research. The method used is a case study. Results: the results of the study showed that the majority of Active ROM respondents were treated for 2 days with a frequency of 5 respondents. Then the results showed that there was a difference in the effect of passive ROM on the length of stay for fracture patients at Sukoharjo Regional General Hospital.